Facilitating primary care non-antiretroviral drug prescribing in people living with HIV: The 'THINK ARV' initiative. (January 2022) - Knox, Chloe; Leak Date, Heather; Lim, Su S; Shaw, Mark; Flynn, Brian; Kendall, Lucy; Vera, Jaime
Objectives: Older people living with HIV (PLWH) have higher rates of multimorbidity, polypharmacy and an associated increased risk of potential drug–drug interactions (DDIs). We describe the development, implementation and evaluation of an intervention to increase community prescribers' access to specialist prescribing advice. Methods: Phase One: a survey evaluating General Practitioners' (GPs') knowledge of, and confidence detecting DDIs affecting PLWH, was circulated to eight General Practices in one UK city. Phase Two: co-production was used to develop the THINK ARV intervention for prescribers in city-wide General Practices: a dedicated mobile phone and e-mail advice service staffed by HIV specialist pharmacists. Queries were audited for 6 months pre- and post-intervention. A user-satisfaction survey was emailed to enquirers. Results: Phase One: 42 GPs responded, of whom 62% requested further support identifying DDIs among PLWH. Phase Two: the number of queries received increased from 25 (6 months before 'THINK ARV' launch) to 63 in the following 6 months (152% increase). 94% of the queries were specifically about DDIs. Conclusions: Increasing community prescribers' access to specialist telephone and e-mail advice resulted in increased awareness and detection of DDIs. Similar interventions could be embedded within different healthcare settings to optimise medicines and avoid potential patient harm.